2022
DOI: 10.22541/au.166066188.83054562/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coupling Effect and Superposition Law in Soil Treatment Systems Incorporating Vacuum Preloading

Abstract: In previous published literatures it was stated that superposition law might be valid for ground improvement techniques consisting of prefabricated vertical drains (PVDs) along with surcharge and vacuum preloading. Even some professional geotechnical engineers might think of this false idea that superposition law might be valid in such ground improvement techniques. It was shown that the superposition law is not valid because of the hydro-mechanical coupling interactions which exist between vacuum and surcharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In addition, the vacuum preloading 2D multi-drain plane simulation was conducted by Pardsouie et al [19] the model used Geostudio with constant value of vacuum pressure and also without smear zone showed that there was a good correlation between the prediction of settlement and the measurements in the field except that in the first 50 days. That simulation results gave overestimate the settlement value (Figure 11).…”
Section: • Stage Of Interpretation Of the Results Of Monitoringmentioning
confidence: 99%
“…In addition, the vacuum preloading 2D multi-drain plane simulation was conducted by Pardsouie et al [19] the model used Geostudio with constant value of vacuum pressure and also without smear zone showed that there was a good correlation between the prediction of settlement and the measurements in the field except that in the first 50 days. That simulation results gave overestimate the settlement value (Figure 11).…”
Section: • Stage Of Interpretation Of the Results Of Monitoringmentioning
confidence: 99%